Reference intervals of common serum analytes of Hong Kong Chinese. Issue 5 (25th April 2008) - Chan, A O K; Lee, K C; Leung, J N S; Shek, C C
Abstract : Aim: Setting up reference intervals from the local service populations is one of the major responsibilities of clinical laboratories. Yet, this task is difficult to achieve because it is costly and time consuming when compared with validating reference intervals from assay manufacturers. Methods: Following the recommendations of the International Federation of Clinical Chemistry, healthy local Chinese adults were recruited to set up reference intervals for common serum analytes. Statistical methods recommended by the National Committee for Clinical Laboratory Standards were used for defining the reference limits. Results: Data from 335 subjects were analysed. The reference intervals set up were broadly similar to those provided by the assay manufacturer, except for sodium and potassium. Glomerular filtration rate was estimated by the modification of diet in renal disease equation, with or without modification for Chinese. Body mass index had a significant impact on serum urate and alanine aminotransferase levels. Conclusion: Reference intervals of common serum analytes have been set up for the local Chinese population. A good example of quality laboratory service has also been set up to provide clinicians with reliable reference intervals that they can confidently rely on for the diagnosis and management of patients.